University quality and other educational experiences as determinants for earnings - Lee, Wei Jhin Eugene (2016)
Conventional studies on economics of education have focused on the effect of educational quantity on wages. We focus on the quality, in particular university quality. This is pertinent considering the recent changes in Singapore’s university education landscape. As the government initializes decentralization to push for a more market-based higher education sector, more Singaporean students are undertaking full-time degree programmes at private higher education institutions. This paper studies the returns to university quality and other educational experiences in Singapore. After using Instrumental Variable method to treat for expected endogeneity issues, we find that the returns to university quality is significant and positive for both starting wage and current wage of business school graduates in Singapore. We also examine the returns to university educational experiences such as internship and class of honors. We obtain positive significant estimates albeit smaller size of coefficients than expected.